2014
DOI: 10.1007/s00261-014-0215-9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging of the liver: comparison of image quality between monopolar and bipolar acquisition schemes at 3T

Abstract: In comparison with past studies performed at 1.5T, when using a modern 3T system, we observed improved image quality of liver DWI using a monopolar, rather than a bipolar, acquisition scheme, largely attributed to higher eSNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The ADC values calculated in the present study are within the range reported in the literature . ADC values were higher in the left than in the right hepatic lobe in both sequences and breathing schemes, which is consistent with the literature .…”
Section: Discussionsupporting
confidence: 92%
“…The ADC values calculated in the present study are within the range reported in the literature . ADC values were higher in the left than in the right hepatic lobe in both sequences and breathing schemes, which is consistent with the literature .…”
Section: Discussionsupporting
confidence: 92%
“…In the recent literature, an increasing number of reduced FOV DWI applications with reduced blurring and higher spatial resolution than ss-EPI have been reported, amongst others of the prostate, 9 pancreas, 10 spinal cord, 12 neck 13 and liver imaging. 11 The required number of k-space lines is decreased by reducing Figure 2. Diffusion-weighted imaging using single-shot echo-planar diffusion-weighted imaging (a)-(c), readout segmentation echo planar imaging (d)-(f), reduced field of view echo planar imaging (g)-(i) and corresponding T1-weighted post-contrast T1-weighted (j) and (k) images as well as T2-weighted images (l) in a 34-year-old patient with acute optic neuritis of the left eye.…”
Section: Discussionmentioning
confidence: 99%
“…8 The second promising technology is reduced field-of-view DWI (rFOV-EPI), also called 'inner volume imaging' or 'zoomed DWI'. Zoomed DWI has been reported with improvement of image quality in several organ systems, amongst others the prostate, 9 pancreas, 10 liver, 11 spinal cord 12 and neck. 13 The aim of this study was to evaluate the role of advanced DWI imaging in ON using a high-resolution rs-EPI and rFOV-EPI sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the overall image quality and the level of confidence to establish diagnosis, the conventional MRI was rated significantly higher (rating 3.6 versus 3.3). Interestingly, Rosenkrantz et al report similar results in a recent study in liver imaging [27]. While the majority of the groups could improve their imaging quality using dual-source transmission, Rosenkrantz et al observed higher image quality of the liver DWI using a monopolar scheme.…”
Section: Discussionmentioning
confidence: 52%